Research on pricing strategy of dual-channel supply chain based on blockchain technology under carbon trading - Jiang, Lan; Zhou, Bingji (International Journal of Global Economics and Management, 2024)
In the context of the dual-carbon goal, it is of great significance to study the application of blockchain technology in the dual-channel supply chain under the carbon trading mechanism for the carbon emission reduction of enterprises and the overall profit maximization of the supply chain.In this paper, two decision models of the supply chain under secondary carbon trading are constructed to analyze the two cases of whether to adopt blockchain technology. Stackelberg model is used to study the impact of blockchain technology on the pricing decision of the dual-channel supply chain under carbon trading, and the two models are compared and analyzed.According to the research results, after the application of blockchain technology, wholesale prices, direct sales prices, retail prices, and profits of retailers and manufacturers have increased compared with the non-use of blockchain technology, which is conducive to promoting the development of carbon emission reduction for manufacturers.